Pengaruh Risiko Bisnis, Struktur Aset, Dan Pertumbuhan Penjualan Terhadap Struktur Modal Perusahaan Manufaktur Sektor Barang Konsumsi Yang Terdaftar Bei Tahun 2016-2021 - Siti Nur Mismawati; Widhian Hardiyanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The era of globalization has brought significantly increased economic competitiveness. Companies are required to continue to develop their business. Determining the capital structure is very important for every company. Capital structure decisions can influence the assessment of a company's financial capability by knowing the aspects that can affect a company's capital structure. The purpose of this research was conducted to examine the effect of business risk, asset structure, and sales growth on the company's capital structure partially and simultaneously. The population used in this study is a consumer goods sub-sector manufacturing company listed on the Indonesia Stock Exchange from 2016 to 2021. The sampling technique used purposive sampling, in order to obtain 25 companies that were used as samples in the research. The data analysis technique used in this research is multiple regression analysis. Based on the results of this research, it is known partially that business risk has a significant negative effect on the company's capital structure, while asset structure and sales growth have a significant positive effect on the company's capital structure. Simultaneously, business risk, asset structure, and sales developments influence the company's capital structure. Keywords: Capital Structure, Business Risk, Asset Structure, Sales Growth, Manufacturing Company.